Assessment of the No Plastic Policy Implementation: A Basis to Plastic Waste Management Action Plan - Valenzuela, Victoria P.; Sultan, Lianne Mar DC; Calatrava, Ma. Cecilia A.; Esguerra, Pauline G.; Montero, Diane Grace B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This paper assessed the extent of the implementation of the Provincial Ordinance 2012-09 or the No Plastic Policy in the Municipality of Balagtas, Bulacan. Since plastic waste is one of the evident issues in the municipality, the study aimed to assess the extent and determine the challenges encountered in the implementation of the No Plastic Policy which was signed in order to address the issues related to plastic wastes. The extent of the implementation of the policy was gathered through survey questionnaires distributed to business sectors and households while semi-structured interviews were conducted among the key implementers to determine the challenges encountered. The findings of the study showed that the extent of the implementation of the No Plastic Policy was somewhat implemented and the challenges encountered include costly and limited alternatives; lack of clarity in the operational guidelines; non-compliance of the residents; and lack of strict implementation efforts. Thus, the findings of the study showed that there is a need to strengthen the existing ordinance in the Municipality of Balagtas, Bulacan.